Facilitative Parenting Of Adolescent Self Disclosure : Pengasuhan Fasilitatif Orang Tua Terhadap Keterbukaan Diri Remaja - Amita, Nindy; Wahyuningsih, Hepi (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to find out empirically whether there is a relationship between facilitative parenting and adolescent self-disclosure. The hypothesis used is that there is a positive relationship between facilitative parenting and adolescent self-disclosure. Where the higher the level of concern, the higher the level of self-disclosure of adolescents when they are high and concern is low, the lower the self-disclosure of adolescents. The research subjects were students living with their parents, female and male and aged 15-18 years. The number of research subjects was 82 people, consisting of 35 women and 27 men. The adolescent self-disclosure scale that based on the theory of Buhrmester & Prager in Bauminger (2008). Parenting scale based on theory and Grolnick (2009). Method of data analysis using product moment correlation technique. The results of the analysis have a normal data distribution with a linear correlation. While the correlation coefficient between maternal parenting and adolescent self-disclosure to mothers is 0.494 and p = 0.000 (p <0.05) with an effective contribution of 0.244. While the father's self-disclosure analysis obtained the results of 0.727 and p = 0.000 (p <0.05) with an effective contribution of 0.529